Typification of the names Rhopalocnemis phalloides and Phaeocordylis areolata (Balanophoraceae) - Cardoso, Leandro Jorge Telles; Wieringa, Jan Johannes; Braga, João Marcelo Alvarenga (Phytotaxa, 2018)
We present nomenclatural notes and designate lectotypes for Rhopalocnemis phalloides and its synonym Phaeocordylis areolata.